DETERMINAN REVISIT INTENTION PENGUNJUNG MUSEUM DALAM PERSPEKTIF EXPERIENTIAL MARKETING - Gede Suparna; I Gede Riana (EKUITAS (Jurnal Ekonomi dan Keuangan), 2022)
This study aim to analyze the influence of visitor experience on satisfaction and the revisit intention. The population were visitors to the museum using the accidental sampling approach. accidental sampling is a technique of determining the sample by chance, that is, anyone who happens to meet the researcher can be used as a sample, if it is considered suiTabel as a data source. The number of samples used was 216 visitors that valid for analized before data collection, the instruments used in the study were tested first using validity and reliability tests to make sure the instruments were valid and reliable. The analytical used is descriptive and inferential analysis with the Warp Partial Least Square approach. The results showed that experiential marketing had a significant effect on learning in museums, visitor satisfaction, and the desire to return. Learning in museums has a significant effect on visitor satisfaction, but has a weak effect on the desire to visit again. Furthermore, visitors who are satisfied tend want to visit again.